Springtails - P.G. Koehler; F.M. Oi; M.L. Aparicio (EDIS)
This document provides an overview of springtails, minute wingless insects in the Order Collembola. It describes their biology, appearance, and habits, highlighting their presence in moist environments and their role in decomposing organic material. The article outlines the problems springtails can cause, such as invading homes and damaging young seedlings. Control measures are discussed, including indoor and outdoor strategies like reducing moisture, sealing entry points, and using insecticides. This comprehensive guide aims to help homeowners manage springtail infestations effectively. Publication date: October 1994.